The Macroeconomic Impacts of Digitalization in Sub-Saharan Africa : Evidence from Submarine Cables - Simione, Felix; Li, Yiruo (Washington, D.C. : International Monetary Fund, 2021)
The Macroeconomic Impacts of Digitalization in Sub-Saharan Africa: Evidence from Submarine Cables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Employment; Foreign Exchange; Informal Economy; Underground Econom; Unemployment